Toxins in Botanical Drugs and Plant-derived Food and Feed – from Science to Regulation: A Workshop Review - Schrenk, Dieter; Allemang, Ashley; Fahrer, Jörg; Harms, Henrik; Li, Xilin; Lin, Ge; Mahony, Catherine; Mulder, Patrick; Peijnenburg, Ad; Pfuhler, Stefan; Punt, Ans; Sievers, Hartwig; Troutman, John; Widjaja, Frances (Planta Medica, 2024)
In September 2022, the 3rd International Workshop on pyrrolizidine alkaloids (PAs) and related phytotoxins was held on-line, entitled ʼToxins in botanical drugs and plant-derived food and feed – from science to regulationʼ. The workshop focused on new findings about the occurrence, exposure, toxicity, and risk assessment of PAs. In addition, new scientific results related to the risk assessment of alkenylbenzenes, a distinct class of herbal constituents, were presented. The presence of PAs and alkenylbenzenes in plant-derived food, feed, and herbal medicines has raised health concerns with respect to their acute and chronic toxicity but mainly related to the genotoxic and carcinogenic properties of several congeners. The compounds are natural constituents of a variety of plant families and species widely used in medicinal, food, and feed products. Their individual occurrence, levels, and toxic properties, together with the broad range of congeners present in nature, represent a striking challenge to modern toxicology. This review tries to provide an overview of the current knowledge on these compounds and indicates needs and perspectives for future research.
Keywords: Alkenylbenzenes; carcinogenicity; genotoxicity; pyrrolizidine alkaloids; relative toxic potency; risk assessment